Effect of thermal and surface chemical treatment on the cyclic oxidation behavior of 7039 aluminum alloy used in aerospace armor applications. (2021) - Ali Fageehi, Yahya; Saminathan, Rajasekaran; Venugopal, Gunasekaran; Valder, James; Kumar, Hemanth; Ravishankar, K.S.
Abstract: 7039 Aluminum alloy is subjected to artificial aging (T6 treatment) at temperatures namely 80, 100, 120, 140, 160 °C for various time periods up to 100 h. Based on the Brinell Hardness measurements the artificially aged alloys are categorized into three groups namely under aged, peak aged and overaged based. The specimens from the alloy groups are further subjected to cyclic oxidation measurements at temperatures namely 100, 200 and 300 °C. The cyclic oxidation measurements in atmospheric air, revealed that the pre temperature history of the artificially aged alloy has an influence on the cyclic oxidation behavior of the 7039 Aluminum alloy as the under aged alloy showed greater tendency for cyclic oxidation. A surface chemical treatment is employed to coat the alloy by CeO2 ceramic coating through chemical bath technique. Cyclic oxidation tests, X-RD and SEM analysis of the 7039 Aluminum alloy specimens with and without ceramic coatings are carried out. Interestingly, the ceramic coated 7039 Aluminum alloy showed greater resistance to oxidation when compared to that of artificially aged alloy specimens.